MANAJEMEN PEMERINTAHAN DALAM PELAYANAN KESEHATAN PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA (PIS-PK) DI KECAMATAN PEKANBARU KOTA KOTA PEKANBARU TAHUN 2017-2018 - Zahratul Aini; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The aim of the PIS-PK Activity is to improve the quality of Indonesian human life and make it the main program of health development. To develop programs and activities based on management. Government management in PIS-PK health services in Pekanbaru City, Pekanbaru City District, 2017-2018. This study uses qualitative research methods with descriptive types. This method aims to get a true picture of Government management in PIS-PK health services in Pekanbaru City, Pekanbaru City District, 2017-2018. The study found that PIS-PK management was carried out through a structured process in accordance with the management of the Republic of Indonesia Ministerial Regulation of Health by conducting health data collection for all family members, blinded and managing Puskesmas databases, Analyzing, formulating health problem interventions, and arranging Puskesmas plans. in promotive, preventive, curative, and rehabilitative efforts, Carrying out health services (inside and outside the building) through the life cycle approach, Carrying out information systems and puskesmas reporting. Factors that inhibit are HR, PIS-PK Program Application, Socialization, and Infrastructure facilities. The four components have been implemented as such so that the Government management in the PIS-PK health services in Pekanbaru Kota District is well implemented.Keywords: Government Management, PIS-PK